2015
DOI: 10.1016/j.copsyc.2015.01.020
|View full text |Cite
|
Sign up to set email alerts
|

Psychological treatment of depressive rumination

Abstract: Depressive rumination is the tendency to repeatedly dwell on the causes and meanings of negative symptoms, feelings, and problems. It has been robustly implicated as an important mechanism in the onset and maintenance of depression, and has recently been proposed as a potential therapy target to improve treatment efficacy. I describe emerging trial research on psychological therapies that target rumination, which provides encouraging preliminary evidence that rumination-focused interventions may enhance treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(64 citation statements)
references
References 45 publications
0
61
0
3
Order By: Relevance
“…Regards psychological treatment, generic interventions to reduce RNT are currently being tested, such as rumination-focused CBT, mindfulness-based CBT, meta-cognitive therapy, and cognitive bias modification (Watkins, 2015). A recent systematic review of treatments to reduce rumination and worry (Querstret and Cropley, 2013) showed that mindfulness-based and cognitive-behavioral interventions may be effective in the reduction of both rumination and worry.…”
Section: Discussion Of Research Findingsmentioning
confidence: 99%
“…Regards psychological treatment, generic interventions to reduce RNT are currently being tested, such as rumination-focused CBT, mindfulness-based CBT, meta-cognitive therapy, and cognitive bias modification (Watkins, 2015). A recent systematic review of treatments to reduce rumination and worry (Querstret and Cropley, 2013) showed that mindfulness-based and cognitive-behavioral interventions may be effective in the reduction of both rumination and worry.…”
Section: Discussion Of Research Findingsmentioning
confidence: 99%
“…Nolan-Hoeksema (2000) ha estudiado la relación entre la rumiación y los trastornos emocionales y ha comprobado que participantes sanos que puntuaban alto en rumiación tendían a desarrollar al año siguiente más sintomatología depresiva que los que no utilizaban la rumiación como mecanismo regulatorio. En esta misma línea, también se ha identificado la rumiación como un factor predisponente al inicio y mantenimiento de la depresión, siendo, por tanto, un objetivo específico en los tratamientos para esta condición clínica (Watkins, 2015). Cambio cognitivo desadaptativo.…”
Section: Resultsunclassified
“…Nolan-Hoeksema (2000) ha estudiado la relación entre la rumiación y los trastornos emocionales y ha comprobado que participantes sanos que puntuaban alto en rumiación tendían a desarrollar al año siguiente más sintomatología depresiva que los que no utilizaban la rumiación como mecanismo regulatorio. En esta misma línea, también se ha identificado la rumiación como un factor predisponente al inicio y mantenimiento de la depresión, siendo, por tanto, un objetivo específico en los tratamientos para esta condición clínica (Watkins, 2015). àgorA de sAlut.…”
Section: La Regulación Emocional En Los Trastornos Emocionales Una Punclassified